2015
DOI: 10.1186/s13104-015-1413-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of waterpipe use amongst adolescents in Northern Sweden: a survey of use pattern, risk perception, and environmental factors

Abstract: BackgroundDeterminants of waterpipe use in adolescents are believed to differ from those for other tobacco products, but there is a lack of studies of possible social, cultural, or psychological aspects of waterpipe use in this population. This study applied a socioecological model to explore waterpipe use, and its relationship to other tobacco use in Swedish adolescents.MethodsA total of 106 adolescents who attended an urban high-school in northern Sweden responded to an anonymous questionnaire. Prevalence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
2
20
1
2
Order By: Relevance
“…The semi structured interview guides were thematic and flexible and probing was used. The interview guide was developed and tested by the research team based on an adapted version of the socioecological model for health promotion (Ramji et al, 2015). All interviews were conducted in Swedish and were transcribed and translated into English by professionals who are fluent in both languages and had research experience.…”
Section: Interview Guidementioning
confidence: 99%
“…The semi structured interview guides were thematic and flexible and probing was used. The interview guide was developed and tested by the research team based on an adapted version of the socioecological model for health promotion (Ramji et al, 2015). All interviews were conducted in Swedish and were transcribed and translated into English by professionals who are fluent in both languages and had research experience.…”
Section: Interview Guidementioning
confidence: 99%
“…The smoke then bubbles through a jar filled with water and is ultimately inhaled. Although waterpipe smoking is a cultural custom in many Middle‐Eastern countries such as Bahrain, Lebanon, Qatar, Saudi Arabia, and United Arab Emirates; this form of smoking has gained popularity, particularly among the youth, in many Western countries including Hong Kong, Sweden, United Kingdom, and the United States . Results from a recent study showed that waterpipe smoking is not less harmful than cigarette smoking, and waterpipe smokers (WS) are as susceptible to periodontal destruction as conventional cigarette smokers (CS).…”
Section: Introductionmentioning
confidence: 99%
“…Although waterpipe smoking is a cultural custom in many Middle-Eastern countries such as Bahrain, Lebanon, Qatar, Saudi Arabia, and United Arab Emirates; [13][14][15][16] this form of smoking has gained popularity, particularly among the youth, in many Western countries including Hong Kong, Sweden, United Kingdom, and the United States. [17][18][19][20] Results from a recent study 14 showed that waterpipe smoking is not less harmful than cigarette smoking, and waterpipe smokers (WS) are as susceptible to periodontal destruction as conventional cigarette smokers (CS). Similarly, in a clinical study on dental implants, Al-Harthi et al 13 compared the peri-implant soft tissue inflammatory parameters (plaque index [PI], bleeding on probing [BOP], probing depth [PD], and CBL) among WS, CS, and never-smokers (NS).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 100 million people use waterpipe on a daily basis (Wolfram et al, 2003); and this form of smoking causes approximately 5 million deaths per annum (Neergaard et al, 2007). WS is a cultural custom in many Middle-Eastern countries including Bahrain, Egypt, Jordan, Qatar, Saudi Arabia, Syria, Turkey, Lebanon, and the United Arab Emirates (Natto, 2005, Moh’d Al-Mulla et al, 2008, Maziak et al, 2009, Borgan et al, 2014, Jaghbir et al, 2014, Almutairi, 2015, Maziak et al, 2015a, Javed et al, 2016a); However, this form of tobacco smoking has gained popularity in many other countries including Canada, Denmark, Greece, India, Pakistan, Malaysia, Sweden, United Kingdom and the United States (U.S.) (Jensen et al, 2010, Kassim et al, 2014, Ramji et al, 2015, Hammal et al, 2016, Sidani et al, 2016). In the U.S., the Tobacco Products and Risk Perceptions Surveys of 2014 and 2015 found a prevalence of 15.8% of ever smoking waterpipe among adults (Majeed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%